Capital Structure Research Trends : A Bibliometric Review - Reni Marlina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study uses a bibliometric analysis based on Scopus data to map the literature on capital structure development for the period 2018–2023. Using articles from Q1 and Q2 indexed journals selected using the PRISMA 2020 guidelines, this study examines publication trends, dominant keywords, and theme evolution using VOSviewer. The results show a shift in focus from classical theories (such as trade-off and pecking order) to contemporary issues such as ESG, green finance, and digitalization. In addition, the majority of studies are still dominated by developed countries, while contributions from developing countries are still limited. These findings highlight the need for a contextual approach and updating of theoretical models in capital structure research, as well as providing an initial foundation for empirical studies in the technology sector of developing countries.